2014
DOI: 10.1093/cid/ciu919
|View full text |Cite
|
Sign up to set email alerts
|

End-Stage Renal Disease Among HIV-Infected Adults in North America

Abstract: The risk of ESRD remains high among HIV-infected individuals in care but is declining with improvements in virologic suppression. HIV-infected black persons continue to comprise the majority of cases, as a result of higher viral loads, comorbidities, and genetic susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
108
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(113 citation statements)
references
References 35 publications
2
108
2
1
Order By: Relevance
“…29 Kidney dysfunction is often multifactorial in older HCV-infected patients. Besides the less common immune-mediated renal damage secondary to cryoglobulinemia, lifestyle factors, such as substance abuse 30,31 and co-morbid diseases common with aging, such as diabetes and hypertension 31 are also important determinants of worsening renal function in HCV-infected persons.…”
Section: Hcv Infection and Extra-hepatic Clinical Outcomesmentioning
confidence: 99%
“…29 Kidney dysfunction is often multifactorial in older HCV-infected patients. Besides the less common immune-mediated renal damage secondary to cryoglobulinemia, lifestyle factors, such as substance abuse 30,31 and co-morbid diseases common with aging, such as diabetes and hypertension 31 are also important determinants of worsening renal function in HCV-infected persons.…”
Section: Hcv Infection and Extra-hepatic Clinical Outcomesmentioning
confidence: 99%
“…In the North American AIDS Cohort Collaboration on Research and Design study, endstage renal disease risk was significantly higher for black patients, those with unsuppressed viral loads while on ART, those with lower CD4 þ counts, and those with a history of AIDS. Three well established risk factors for end-stage renal disease in the general population-diabetes mellitus, hypertension, and HCV infection-were also highly linked to the risk of end-stage renal disease [57].…”
Section: Renal Insufficiencymentioning
confidence: 99%
“…Similarly, another study reported that viral suppression over time was associated with favorable changes in estimated GFR in subjects with advanced HIV disease at baseline [11]. Additionally, a recent study from a North American consortium of HIV cohorts reported that the incidence of end-stage renal disease (ESRD) among HIV-positive subjects that maintained durable viral suppression was similar to age-, sex-, and race-matched ESRD rates in the general population [12]. In contrast, we found no association between current CD4 count and baseline iGFR or iGFR slope, consistent with a prior report [6].…”
Section: Discussionmentioning
confidence: 99%